CHARACTERIZATIONS OF WOMEN WIDOWED IN THE SHORT STORY NAMANYA, MASSA, TARIAN HAMIL DAN PENYAIR BULAN, AND NORHAYATI (Literary Review Cross Reference) - Nur Ahid Prasetyawan Purnomosidhi; Ninuk Lustyantie (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
ABSTRACTThis research aimed to gain a deep understanding of comparative characterizations, household status, occupation or profession, and socio-cultural background of the third figure women widowed in a collection of short stories (short story), a literary review cross reference. This research seeks to understand the phenomenon of characterizations of women widowed in three short stories that are then compared between the three. Approach this research in the form of a qualitative approach and methods used are content analysis methods. The process of data analysis in this research is not based on an effort to test the hypothesis, but rather attempted to develop a theory or framework of thinking based on the theory of literary sociology, so researchers retain a major role as a tool research. Data sources the study consists of three short stories namely (1) â€œNamanya, Massaâ€, by Ratna Indraswari Ibrahim, a short story from Indonesia, (2) â€œTarian Hamil dan Penyair Bulanâ€ by Johari Tarif, short stories from Malaysia, (3) and